A Multicenter Retrospective Study on Real-World Outcomes of ceftazidime-avibactam in gram-negative bacterial infection in Taiwan - Tsung Ying Zegma Yang; Yee Chun Chen; Yi Tsung Lin; Ching Tai Huang; Po Yu Liu; Po Liang Lu (Journal of Global Antimicrobial Resistance)
Ceftazidime-avibactam (CAZ-AVI) has been launched in Asian countries for five years, local real-world data about infections, patient characteristics, efficacy, and safety of CAZ-AVI in gram-negative bacterial infection is limited. We conducted a multicenter, retrospective cohort study to investigate the clinical characteristics, microbiology, and outcomes of patients treated with CAZ-AVI for gram-negative bacterial infection in Taiwan. Among the 472 patients treated by CAZ-AVI, 44.9% had respiratory tract infections, 21.2% had complicated urinary tract infections, 12.5% had complicated intra-abdominal infections, and 9.5% had primary bacteremia. Most patients receiving ceftazidime/avibactam in Taiwan are older, have a high SOFA score (mean 8.4), and have a high Charlson Comorbidity Index score (75.1%). 90% (425/472) of CAZ-AVI were used as targeted therapy for pathogens including Klebsiella pneumoniae (304/472, 64.4%), Pseudomonas aeruginosa (84/472, 17.8%), Escherichia coli (39/472, 8.3%), and Enterobacter spp. (11/472, 2.3%). The overall clinical success rate is 58.1%, and the in-hospital mortality rate is 41.1%. The logistic regression model revealed a significantly higher clinical success rate for those who initiated CAZ-AVI within 24 - 48 hours than those receiving CAZ-AVI > 72 hours. The multivariate logistic regression analysis revealed that receiving immunomodulators, higher SOFA score, and Enterobacter spp. infection were the significant factors associated with in-hospital mortality.